PENINGKATAN KESADARAN TERHADAP PROTOKOL KESEHATAN PADA ANAK-ANAK PANTI ASUHAN AISYIAH BANDAR KLIPPA KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Aprilza Aswani; Orli Binta Tumanggor; Annalisa Sonaria Hasibuan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
The Covid-19 pandemic is a dangerous epidemic and has become a global threat. To prevent the transmission of this disease, health protocols must be strictly applied. Based on observations made at the Aisyiah Bandar Klippa Orphanage, Percut Sei Tuan District, Deli Serdang Regency, there is a problem that is still low awareness of health protocols as an effort to prevent the transmission of Covid-19, such as using masks, washing hands or using hand sanitizers after touching foreign objects. To build awareness of the health protocol, it is necessary to carry out activities through discussion, socialization, and counseling. Participants in this activity were 50 people consisting of orphanages and children from the Aisyiah Bandar Klippa Orphanage, Percut Sei Tuan District, Deli Serdang Regency. The method used in community empowerment is counseling and socialization about the importance of implementing the Covid-19 prevention health protocol as well as question and answer to listen to the complaints and needs of partners effectively. Based on the results of monitoring, there is an increase in the awareness of children and orphanages in implementing the Covid-19 prevention health protocol, such as using hand sanitizers and using masks when leaving the orphanage.